(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the effects of periodontal treatment on glycaemic control in patients with type II diabetes mellitus. Materials and Methods: This study was conducted in 40 patients (19 men and 21 women) with periodontitis. The control group, which included 20 patients who had stage I-II periodontitis but were otherwise healthy, underwent periodontal clinical measurements before and after periodontal treatment. The diabetic group, which included 20 patients with type II diabetes mellitus and stage I-II periodontitis, also underwent periodontal clinical measurements before and after periodontal treatment. The study was conducted in patients between the ages of 18 and 69 years. The plasma blood glucose, C-reactive protein (CRP), and glycated haemoglobin (HbA1c) levels were measured at baseline and 3 months. The probing pocket depth (PPD), plaque index (PI), and gingival index (GI) were measured from four surfaces of the relevant teeth of all the patients who participated in the study to determine the periodontal status. The collected numerical data were statistically analysed. Results: The fasting plasma glucose, CRP, and HbA1c levels significantly decreased in the diabetic group three months after periodontal treatment (p<0.001). There was a statistically significant difference in the change in the PPD, PI, and GI from baseline to 3 months between the two groups (p < 0.05). Conclusion: In our study, periodontal treatment positively contributed to glycaemic control by significantly decreasing fasting plasma glucose, HbA1c, and CRP values in patients with type II diabetes.